Assessment of Culture Potentialities of Hybrids from Crosses between Oreochromis niloticus and Sarotherodon melanotheron Reared in Ebrié Lagoon (Côte d’Ivoire) Using Geometric Morphometric Approach: An Advance Study - Bopo, Z. S. O.; Sokouri, D. P.; Amon, Y. N.; Boua, A. C.; Assanvo, N. S. P. (Recent Research Advances in Biology Vol. 7, 2021)
Culture potentialities of the hybrids from crosses between Oreochromis niloticus (Linnaeus, 1758) and Sarotherodon melanotheron (Rüppel, 1852) were assessed in breeding design through morphological features using geometric morphometric approach. The crosses and rearing procedure, that lasted six months, are performed into a concrete pond at Layo Aquaculture Station. The morphological studies were undertaken with morphometric biomarkers such as average body shape and components of developmental homeostasis (canalisation and developmental stability). Average body shape between groups was investigated using Relative Warps Analysis (RWA) and Canonical Variates Analysis (CVA), whereas canalisation and fluctuating asymmetry were evaluated from ANOVA Procrustes. The results showed that the body shape of the hybrids is intermediate between those of the two parental species and that the reciprocal hybrids of first generation exhibit heterosis in size. Heterosis effects also seem affect positively fluctuating asymmetry and canalisation levels, which mirror developmental compatibilities between hybridising taxa. This hybrid vigor appeared more on the hybrids resulting from crosses between S. melanotheron males and O. niloticus females. In a general way, the morphology of the head of the hybrids is similar to that of the parent O. niloticus and their fins resembled to those of the parent S. melanotheron. Moreover, fluctuating asymmetry in shape does not vary between parental species and hybrids, contrary to fluctuating asymmetry in size, which is lesser in latter. Canalisation was found to be smaller in the hybrids compared to the parental ones. So, these results revealed that the hybrids could benefit from most of accrued advantages of parental species.